Hubungan Konsumsi Makanan Manis Dengan Kejadian Karies Gigi Pada Anak Prasekolah Di TK B RA Muslimat PSM Tegalrejodesa Semen Kecamatan Nguntoronadi Kabupaten Magetan - Sumini Sumini; Bibi Amikasari; Devi Nurhayati (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2014)
Sweet foods is a simple carbohydrate because it is soluble in water and is directlyabsorbed by the body to convert into energy. The problem is almost entirely obtained in10 children experience dental caries. From the preliminary study on 12 March 2014obtained 7 children rarely eat sweet foods, caries gigidan 4 children 3 children notexperienced by charismatic teeth RA Moslem children in the village of Cement District ofPSM Tegalrejo Nguntoronadi Magetan. This study aims to determine the relationship ofsweet food consumption with incidence of dental caries in preschool children in RAMoslem village of Cement District of PSM Tegalrejo Nguntoronadi Magetan.The study was conducted in March to Mei.Metode used in this study arecorrelational and cross-sectional survey design to use. The population of this study are allchildren in the RA's Women PSM Tegalrejo, Cement Village, District, Nguntoronadi,Ponorogo by 33 Children with saturated sampling techniques. Methods of data collectionusing questionnaire and caries examination. Then the data were analyzed with the aid ofcomputerized using statistical test ChiSquare.The results showed almost 26 respondents seluruhya consumption of sweet foods(78.8%) who frequently consume sweet foods. And almost all of 30 respondents (90.9%)had caries g Based on the results of data analysis using Chi-Square test statistic obtainedcorrelation coefficient 0.609 with significance level of 0.000. Because p-value = 0.000<0.05, it can be concluded that Ho is rejected which means that there is a relationshipwith the consumption of sweet foods incidence of dental caries in preschool children inthe RA's Women Psm Tegalrejo Cement Village Subdistrict Nguntoronadi Magetan.The conclusion of this research is almost entirely children experience dentalcaries, and how to prevent it is diligent in cleaning your child's teeth every day iemorning and evening before bed, do counseling to parents on how to prevent dentalcaries, consult and perform routine checks to the dentist.